What is preventing individual climate action? Impact awareness and perceived difficulties in changing transport and food behaviour - Shane Timmons; Ylva Andersson; Maria Lee; Pete Lunn (The Economic and Social Research Institute (ESRI), 2024)
Mitigating climate change requires large and, by historical standards, rapid changes to policy, business processes and individual behaviour. This report examines awareness of and perceived difficulty with individual behaviour change with respect to two actions associated with high levels of emissions: transport and food choice. A nationally representative sample of 1,200 adults completed an online study about everyday transport and food behaviour, run in September 2023. After completing a diary task about the previous day, participants identified the parts of their day that mattered most for their carbon footprint. Answers were elicited via incentivised, open text questions to prevent pre-set options biasing responses. Participants also answered standard survey questions about their use of various modes of transport in a typical week and their consumption of various foods. Participants who reported wanting to change their transport behaviour and diet 'to reduce their carbon footprint' (47 per cent and 42 per cent, respectively) listed reasons why it is difficult for them to do so, again via open text questions.
Keywords: 330; Klimawandel; Verkehrsverhalten; Ernährungsverhalten; Irland